2018
DOI: 10.3389/fpls.2018.01637
|View full text |Cite
|
Sign up to set email alerts
|

NADP-Dependent Malic Enzyme 1 Participates in the Abscisic Acid Response in Arabidopsis thaliana

Abstract: Arabidopsis thaliana possesses three cytosolic (NADP-ME1-3) and one plastidic (NADP-ME4) NADP-dependent malic enzymes. NADP-ME2 and -ME4 show constitutive expression, in contrast to NADP-ME1 and -ME3, which are restricted to particular tissues. Here, we show that NADP-ME1 transcript and protein were almost undetectable during normal vegetative growth, but gradually increased and reached levels higher than those of the other isoforms in the latest stages of seed development. Accordingly, in knockout nadp-me1 ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Hence, the enzyme participates during both seed germination and seedling growth stages. It is also essential to enhance tolerance of drought and saline conditions ( Arias et al, 2018 ). Other proteins involved in the phytohormone-mediated responses that were upregulated by specific bacterial treatments are given in Table 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the enzyme participates during both seed germination and seedling growth stages. It is also essential to enhance tolerance of drought and saline conditions ( Arias et al, 2018 ). Other proteins involved in the phytohormone-mediated responses that were upregulated by specific bacterial treatments are given in Table 3 .…”
Section: Discussionmentioning
confidence: 99%
“…They also play various crucial roles in the plant’s tolerance to abiotic stress [17]. Malic enzyme is known to play diverse roles in the plant notably in its involvement in seed germination and development as well as in the plant’s response to various external stresses [18,19]. The clathrin heavy chain subunits were reported to influence stomatal function, plant growth, and immunity [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that MDHG catalyzes the NAD/NADH-dependent interconversion of the substrates malate and oxaloacetate [ 36 ]. MAOX releases CO 2 and pyruvate from malate and participates in the response of the ABA [ 60 ]. PPDK enhances photosynthesis, carbon assimilation, and abiotic stress tolerance under conditions with elevated CO 2 [ 61 ].…”
Section: Discussionmentioning
confidence: 99%